Strategiczne problemy publicznej szkoły wyższej - Moszkowicz, Mieczysław (Strategic inconveniences at public university, 2006)
The paper presents an approximate result of analysing selected university department. The main results of the analysis are: a) macroeconomic approach - identification of strategic problems in the area of knowledge based economy, b) plan of strategic objectives for the analyzed department.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 222-230